High-resolution microwave studies of ring-structured complexes between trifluoroacetic acid and water. - Ouyang, B; Starkey, T; Howard, B (2007)
The rotational spectra of the complexes between one trifluoroacetic acid molecule and up to three water molecules have been recorded using a pulsed nozzle Fourier transform microwave spectrometer. The unambiguous assignments of them are made on the basis of the agreement between the experimentally determined rotational constants and the theoretical predictions from ab initio calculations using MP2/6-311++G(2df,2pd). All the complexes exhibit hydrogen-bonded ring structures. The fine splittings observed in some of the a-type transitions of the trifluoroacetic acid-H2O dimer were analyzed in terms of the likely tunneling motions of the hydrogens in the H2O molecule. Further calculations of the equilibrium constants for these three hydrated complexes of trifluoroacetic acid were also made to evaluate their fractions against the trifluoroacetic acid monomer in the atmosphere.